Retrofitted Existing Residential Building Design in Energy and Economic Aspect According to Thailand Building Energy Code - Santipont Ananwattanaporn; Theerasak Patcharoen; Sulee Bunjongjit; Atthapol Ngaopitakkul (My University, 2021)
Electrical energy usage in buildings is a challenging issue because many old buildings were not originally built to achieve energy efficiency. Thus, retrofitting old buildings to net-zero buildings can benefit both the owner and electric utilities. In this study, the BEC (building energy code) software was used to evaluate energy aspects of retrofitted buildings in compliance with Thailand’s building energy code to achieve a net-zero energy building. In addition, economic aspects were also studied to verify the feasibility for a project’s owner to invest in a retrofitted existing building. An existing residential building in Thailand was used as a case study. The results in terms of energy after retrofitting existing buildings into net-zero energy buildings show that the total energy consumption can be reduced by 49.36%. From an economic perspective, the investment cost for a retrofitted building can be compensated by energy saving in terms of discounted payback period (DPP) for approximately 4.36 years and has an IRR (internal rate of return) value of 19.23%. This result evidences the potential in both energy and economy for a project’s owner to invest in a retrofitted existing building in compliance with the building code, with potential for implementation with benefits on both electrical utilities and the project’s owner.
Keywords: Retrofitting; Payback period; Building code; Present value; Investment; Building Energy and Comfort Optimization